2000
DOI: 10.1046/j.1365-2699.2000.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

The biogeographical distribution of microfungi associated with three palm species from tropical and temperate habitats

Abstract: The microfungi of three palm species were investigated in their natural habitats and in habitats where the palms were cultivated outside their natural ranges. The palms that were selected differed in their habitats and ecology. Archontophoenix alexandrae is endemic to tropical rainforests in Australia, Cocos nucifera is pan‐tropical and Trachycarpus fortunei occurs in warm‐temperate China. Different assemblages of fungi were found in association with palms in temperate regions as compared to those in tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 28 publications
5
47
1
1
Order By: Relevance
“…For marine fungi studied along a wider latitudinal gradient, Hughes (1974) and Booth and Kenkel (1986) also found that temperature was an important environmental parameter in explaining the latitudinal distribution patterns of marine fungi. Similarly, Taylor et al (2000) and Fröhlich and Hyde (2000) found the palm saprobes from sites of the same latitude/longitude were more similar than sites from different latitudes. Differences in species composition observed in this study are also similar to patterns observed for other groups of organisms sampled along the temperate-subtropical ecotone of the Florida Peninsula.…”
Section: Figmentioning
confidence: 83%
“…For marine fungi studied along a wider latitudinal gradient, Hughes (1974) and Booth and Kenkel (1986) also found that temperature was an important environmental parameter in explaining the latitudinal distribution patterns of marine fungi. Similarly, Taylor et al (2000) and Fröhlich and Hyde (2000) found the palm saprobes from sites of the same latitude/longitude were more similar than sites from different latitudes. Differences in species composition observed in this study are also similar to patterns observed for other groups of organisms sampled along the temperate-subtropical ecotone of the Florida Peninsula.…”
Section: Figmentioning
confidence: 83%
“…This is a confirmation that the complete linkage method performs quite well in cases in which objects form naturally distinct "clumps". [39] HCA does not provide a statistical test of group dissimilarity, but external tests like the Kolmogorov-Smirnov test can be applied for this purpose. This elaboration was done with SAS version 9.1 (SAS Institute Inc., Cary, NC, USA) with the Kolmogorov-Smirnov hypothesis that two groups of observations have identical distributions.…”
Section: Resultsmentioning
confidence: 99%
“…There were few fungi in common among palms from different sites, and fungal compositions on palms from different sites were less closely coherent than those from the same sites. Taylor et al (1999Taylor et al ( , 2000 have also shown variation between geographically separated communities of endophytic fungi in Trachycarpus fortunei and saprobes on other palms.…”
Section: Eucalyptusmentioning
confidence: 95%